The IDEA (International Duration Evaluation of Adjuvant Chemotherapy) Collaboration: Prospective Combined Analysis of Phase III Trials Investigating Duration of Adjuvant Therapy with the FOLFOX (FOLFOX4 or Modified FOLFOX6) or XELOX (3 versus 6 months) Regimen for Patients with Stage III Colon Cancer: Trial Design and Current Status - André, Thierry (Springer US, 2013)
The International Duration Evaluation of Adjuvant Chemotherapy (IDEA) collaboration was established to prospectively combine and analyze data from several randomized trials conducted around the world to answer whether a three-month course of oxaliplatin-based adjuvant therapy (FOLFOX4/modified FOLFOX6 or XELOX) is non-inferior to the current standard six-month treatment for patients with stage III colon cancer, with a primary endpoint of three years disease-free survival. The IDEA steering committee comprises two members from each group coordinating an individual trial and two members from a secretariat who coordinate combining of the data and management of the joint analysis. Members of the IDEA agreed to combine the data from their individual trials to enable definitive analysis consisting of at least 10,500 patients. With accrual of 8,797 patients at the end of February 2013, the IDEA is on track to achieve its accrual objective of at least 10,500 patients by the end of 2013.